2022
DOI: 10.3389/fmed.2022.854338
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case of Acute T Lymphoblastic Leukemia With Mixed Infection of Lethal Invasive Mucormycosis and Multi-Drug Resistant Bacteria

Abstract: Pulmonary mucormycosis (PM) is a rare and life-threatening fungal infection. Here, we report a case of an acute T lymphoblastic leukemia patient with mixed infections of lethal invasive Mucormycosis and multi-drug resistant (MDR) bacteria. After receiving anti-infection drugs to control the patient's fever, he was treated with induction chemotherapy. However, the malignant hematological disease was poorly controlled by the chemotherapy and the patient developed more symptoms of infection. Although the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports (Chen et al, 2021;Wang et al, 2022;Cui et al, 2022;Hu et al, 2022). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al reported on 60 patients with suspected pneumonia in severe immunodeficiency and analyzed the diagnostic efficacy of mNGS versus CMTs for pneumonia (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports (Chen et al, 2021;Wang et al, 2022;Cui et al, 2022;Hu et al, 2022). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al reported on 60 patients with suspected pneumonia in severe immunodeficiency and analyzed the diagnostic efficacy of mNGS versus CMTs for pneumonia (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports ( Chen et al., 2021 ; Wang et al., 2022 ; Cui et al., 2022 ; Hu et al., 2022 ). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Finding hyphae or a positive culture by bronchoscopy and percutaneous biopsy are diagnostic methods for either pulmonary actinomycosis or pulmonary mucormycosis. More recently developed the Metagenomic next generation sequencing (mNGS) in lavage uid can be utilized as a new diagnostic tool [22][23][24] .…”
Section: Imagementioning
confidence: 99%